Intersecções religiosas: Cosmologia e encontro cultural na américa portuguesa quinhentista (1549-1597) - Silva, Daniel Santana Leite da (2017)
The meeting between Indians and Europeans was based on mutual cultural translations, in which each one saw the other according to his own worldview. Followed by the first chroniclers, still fascinated by the discovery of the New World, the missionaries were the main protagonists in the process of understanding the culture of the natives, now seen as pure and apt to be new Christians, now taken by cunning conduct that harmed the contact and their conversion to Christianity. Since the Jesuit order was the main institution in the process of colonization of the faith throughout the XVI - a project carried out between the Portuguese Crown and the Church - these missionaries were responsible for the effort to understand and assimilate the Other in order to convert it effectively. The pursuit of this objective had in the religious language the key to understanding, where the perception of the religion of the natives would allow, from its deconstruction, to build the Christian religion. That said, the purpose of this dissertation is to present how this process of decoding the Tupinambá cosmology from the Euro-Christian predicates, from the first Jesuit experience - the itinerant missions - and the creation of manuals of the faith for the native conversion - as well as the use of Tupã and Anhangã to translate the meaning of God and Devil.